2019
DOI: 10.15283/ijsc18110
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR/Cas9 Edited sRAGE-MSCs Protect Neuronal Death in Parkinson’s Disease Model

Abstract: Background and Objectives Parkinson’s disease (PD) is a fatal and progressive degenerative disease of the nervous system. Until recently, its promising treatment and underlying mechanisms for neuronal death are poorly understood. This study was investigated to identify the molecular mechanism of neuronal death in the substantia nigra and corpus striatum of PD. Methods The soluble RAGE (sRAGE) secreting Umbilical Cord Blood—derived Mesenchymal Stem Cell (UCB-MSC) was gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 34 publications
0
28
0
1
Order By: Relevance
“…49,50 A few papers suggested PD animal model treatment methods; however, all of them applied CRISPR to individual cells as an ex vivo treatment technique. 51,52 Invariably, there are no reports of successful in vivo treatments by delivering CRISPR directly to animals with PD. Our study overcomes several difficulties and demonstrates the possibility of familial PD treatment for the first time in an animal model applying CRISPR to knock out the A53T-SNCA gene in vivo, the direct cause of familial PD.…”
Section: Discussionmentioning
confidence: 99%
“…49,50 A few papers suggested PD animal model treatment methods; however, all of them applied CRISPR to individual cells as an ex vivo treatment technique. 51,52 Invariably, there are no reports of successful in vivo treatments by delivering CRISPR directly to animals with PD. Our study overcomes several difficulties and demonstrates the possibility of familial PD treatment for the first time in an animal model applying CRISPR to knock out the A53T-SNCA gene in vivo, the direct cause of familial PD.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Hu et al have represented a concept of CRISPR-based cell immortalization strategy for mouse MSCs by introducing simian virus SV40 large T antigen into an intrinsic safe harboring site at Rosa26 locus [ 125 ]. In other reports, CRISPR/Cas9 construct was simultaneously delivered with the AAV vector then gene construct that encodes beneficial protein was knock-in into the AAV-specific safe locus such as AAVS1 [ 126 , 127 ]. This AAV-CRISPR/Cas9 genetic engineering platform can induce the stable overexpression of therapeutic factors in MSCs in a relatively simple and safe way.…”
Section: Bioengineering Of Mscs For the Functional Improvementmentioning
confidence: 99%
“…Hu et al demonstrated that CRISPR/Cas9-induced knockout of Keap1 improved anti-oxidation in AT-MSCs [ 63 ]. Introduction of CRISPR/Cas9-edited sRAGE secreting UCB-MSCs reportedly alleviated neuronal degeneration and improved homing to the lesion in Parkinson’s disease animal mice [ 64 ].…”
Section: Main Textmentioning
confidence: 99%